Review jurnal: pola perbandingan pengobatan farmakologi penderita dispepsia di beberapa rumah sakit - Mally Ghinan Sholih; Munir Alinu Mulki; Sophy Wulandari; Putri Wahyu Primasti; Giga Anugerah Arsylrakhmatika; Nurlita Dwi Putri Prihasti; Amanda Maharani; Roudotul Jannah (Journal of Pharmaceutical and Sciences, 2023)
Dyspepsia is a common complaint often found in the community and among patients who come to clinical practice. Symptoms of dyspepsia include abdominal discomfort, nausea, vomiting, burning, bloating in the upper digestive tract, early satiety, fullness after eating, and belching. This literature review compared prescription patterns in dyspepsia patients from several hospitals. The research method began with a literature search through the PubMed and Google Scholar databases within the specified year range and using the keywords dyspepsia, pattern, treatment, and drug. The conclusion is that there are many uses for generic drugs and different types of drugs in treating patients with dyspepsia. Factors influencing the management of dyspepsia in inpatients include gender, reported clinical symptoms, class of antiulcer therapy, differences in the number of drugs, and drug dosage forms.